Penggunaan Gaya Bahasa dalam Teks Narasi pada Buku Pelajaran Bahasa dan Sastra Makassar Siswa SMP/MTs - Faisal Faisal; Salam Salam; Kembong Daeng (Indonesian Journal of Social and Educational Studies, 2022)
This research is a qualitative descriptive study which aims to examine the language style in the narrative text used in Makassar language and literature textbooks for SMP / MTs students using stylistics (language styles). The data source used in this study was the narrative text in Makassar language and literature textbooks for grade IX students of SMP / MTs. The results of this study get the types of language styles based on comparative language styles, namely personification language styles, symbolic language styles, synekdoke language styles, association language styles, methanemical language styles, and euphemism language styles: language styles based on affirmation language styles, namely polisendeton language styles. , asidenton language style, climax language style, repetition language style, anti-climax language style, and litotes language style; and language style based on satire style, namely cynicism and sarcasm.Keywords: Usage, Language Style, Narrative Text